PENTINGNYA PENDIDIKAN MULTIKULTURAL DAN SIKAP TOLERANSI DI LINGKUNGAN BELAJAR - Ilham, Maulidia (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This research employs a descriptive qualitative approach, utilizing literature study methods and data collection techniques based on literature studies. The focus is on multicultural education, a theoretical framework that acknowledges and respects diversity in culture, language, religion, and backgrounds. Despite this, many educational settings still struggle to fully implement multicultural education. The core issue addressed in this study is the relationship between multicultural education and tolerance. The goal of multicultural education is to increase awareness and understanding among students and communities about the significance of respecting differences and valuing cultural diversity in Indonesia. Findings from this research indicate that multicultural education significantly benefits the learning environment. Previous studies have shown that integrating multicultural education into the curriculum can promote tolerance and prevent discrimination stemming from diversity.